Efektivitas Penyaluran Dana Zakat Produktif Untuk Pengembangan Usaha Mikro Mustahik di BAZNAS Kabupaten Garut - Sulthonuddin, Bung Hijaj; Safitri, Hafsah (STAI Al Musaddadiyah Garut, 2025)
The National Amil Zakat Agency (BAZNAS) of Garut Regency has a program for the productive distribution of zakat funds with the hope of long-term benefits. However, in Garut Regency, the community is still unfamiliar with this program. The problem formulation includes a description of the productive zakat distribution, its distribution, and the effectiveness of productive zakat distribution. This research is a qualitative descriptive study aimed at determining the effectiveness of productive zakat fund distribution for micro-business mustahik. Data collection techniques used interviews and documentation. The results of this study can be concluded that the distribution of productive zakat funds to develop micro-business mustahik is 100% included in the Garut Makmur program, with business assistance funds distributed through two methods: potential mapping and proposal submission. Meanwhile, the effectiveness indicators use the theory from Ni Wayan Budiani, namely: program target accuracy, program socialization, program objectives, and program monitoring. The results show that the indicator of program target accuracy is already effective, while the indicators of program socialization, program monitoring, and program objectives are considered not yet effective. Keywords: Effectiveness; Productive Zakat; Mustahik Micro Business;